VD_FINDINFO Jug / 2019 / 360 vom 14. Oktober 2019 - VD Tribunal cantonal (2019)
LOI FÉDÉRALE SUR LA PROTECTION DES ANIMAUX, PROTECTION DES ANIMAUX, VACHE | 111 al. 2 LTF, 82 al. 2 LTF, 28 LPA, 17 let. h OPAn